TECHNOLOGICAL PRINCIPLES OF THE HETEROGENEOUS ALUMINIUM ALLOYS PRODUCTION AT PARTIAL DISSOLUTION OF FAST-COOLED DISPERSE ALLOY - L. P. Dolgij; G. V. Dovnar; A. A. Andrits (Литьë и металлургия)
The article is dedicated to the matters of improvement of special characteristics such as hightemperature strength, corrosion resistance, thermalphysic indices of alloys on the basis of aluminium by means of alloying them by elements of transition group. Influence of concentrations of elements in addition alloy, speed of its cooling, methods of introduction, portions of alloys introduction, content of applied fluxes and other factors on the structure and characteristics at production of heterogeneous aluminium alloys with the purpose of ensuring of high exploitation characteristics of castings is examined.